2014
DOI: 10.3892/or.2014.3481
|View full text |Cite
|
Sign up to set email alerts
|

miR-379/411 cluster regulates IL-18 and contributes to drug resistance in malignant pleural mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is a rapidly fatal malignancy that is increasing in incidence in Japan. In this study, we performed gene and microRNA (miRNA) expression profiling to identify novel therapeutic targets in MPM cells. Based on relative sensitivities to pemetrexed (PEM) and the histone deacetylase (HDAC) inhibitor, vorinostat (SAHA), 211H cells were determined to be the only sensitive MPM cell line out of the 6 tested. On the same series of cell lines, we performed whole genome transcriptomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…vPrevious studies showed that aberrant expression of miRā€379 contributes to cancer development 31, 32, 33. For instance, Khan et al .…”
Section: Introductionmentioning
confidence: 99%
“…vPrevious studies showed that aberrant expression of miRā€379 contributes to cancer development 31, 32, 33. For instance, Khan et al .…”
Section: Introductionmentioning
confidence: 99%
“…Member(s) of the hsa-miR-18114 and hsa-miR-29 families15 exhibit both anticancer and pro-cancer regulation under different clinical conditions, while members of hsa-miR-12616, hsa-miR-12917, hsa-miR-13618, hsa-miR-20419, hsa-miR-66320, hsa-miR-9921, hsa-miR-37822, hsa-miR-9223, and hsa-miR-40924 families are recognized as having anticancer properties under different clinical conditions. Families that contained at least one miRNA found in hAMSC-CM-derived exosomes reportedly exhibit antagonistic roles in numerous cancer types and include hsa-miR-48625, hsa-miR-10026, hsa-miR-10127, hsa-miR-12428, hsa-miR-128529, hsa-miR-13430, hsa-miR-13831, hsa-miR-13932, hsa-miR-14333, hsa-miR-18634, hsa-miR-19335, hsa-miR-20536, hsa-miR-22237, hsa-miR-33838, hsa-miR-33939, hsa-miR-42440, hsa-miR-12741, hsa-miR-2642, hsa-miR-10343, hsa-miR-10744, hsa-miR-12845, hsa-miR-14046, hsa-miR-14447, hsa-miR-15348, hsa-miR-19249, hsa-miR-21250, hsa-miR-21851, hsa-miR-2352, hsa-miR-2553, hsa-miR-37054, hsa-miR-37555, hsa-miR-38156, hsa-miR-41057, hsa-miR-4158, and hsa-miR-9359. These NGS data revealed an enriched miRNA population in hAMSC-CM-derived exosomes that are likely involved in the regulation of different types of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Exceptionally, hAMSC-CM derived exosomal miRNAs demonstrated outstanding diversity, which encompasses numerous anti-cancer miRNAs891011121314151617181920212223242526272829303132333435363738394041424344454647484950515253545556575859, as well as new and poorly investigated miRNAs. In contrast, miRNAs, which are frequently detected in different cancers exosomes (include hsa-miR-105, hsa-miR-214, hsa-miR-92, hsa-miR-21, hsa-miR-29, hsa-miR-9, hsa-miR-222)6364, were either absent or showed very nominal expression in hAMSC-CM derived exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that miR-379 levels are lower in circulating blood from patients with atherosclerotic coronary artery disease 18. In cancer studies, miR-379 was found to inhibit breast cancer cell proliferation by regulating cyclin B1 expression;21 Yamamoto reported that miR-379 inhibited cell growth of malignant pleural mesothelioma by targeting interleukin 18 23. In addition, miR-379 also exhibited a tumor-suppressive function in liver cancer 22.…”
Section: Discussionmentioning
confidence: 99%
“…miR-379 has also been found to inhibit cell growth in certain types of cancers including breast cancer, malignant mesothelioma, and liver cancer 212223. In this study, we investigated the functional role of miR-379 in the growth of VSMCs.…”
Section: Introductionmentioning
confidence: 99%